QTL-mapping of genomic regions controlling gluten strength in durum (Triticum turgidum L. var. durum) - Elouafi I.; Nachit M.; Elsaleh A.; Asbati A.; Mather D.E. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
Gluten strength is the main determinant of the end-use quality in durum. Wheat gluten strength is affected by genetic variation at genes coding for gliadins and glutenins, and by environmental factors. We grew 110 recombinant inbred lines of the cross Jennah Khetifa x Cham1 in 13 environments (sites and years), and analyzed gluten strength in the resulting grain samples. We used Simple Interval Mapping (SIM) and simplified form of Composite Interval Mapping (sCIM) to estimate the positions of QTL and QTL x environment interactions on a 319-marker linkage map. Five QTL were detected. Two of these are on chromosome 6B, one (near Xgwms644) with a main effect across environments and one at XPstIaagMseIcga9 with a QTL-by-environment interaction but no significant main effect. Together, these five QTL explained 35 per cent of the total phenotypic variation for gluten strength. Our results show a clear combined effect of genes, precipitation, nitrogen fertilization, drought, and heat on gluten strength.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)